How pre‐service teachers' personality traits, self‐efficacy, and discipline strategies contribute to the teacher–student relationship. (8th July 2013) - de Jong, Romi; Mainhard, Tim; van Tartwijk, Jan; Veldman, Ietje; Verloop, Nico; Wubbels, Theo
<x xml:space="preserve">Abstract</x> Background Although the teacher–student relationship is a well‐documented phenomenon, few attempts have been made to identify its predictors. Research has mainly focused on in‐service teachers, less is known about characteristics of pre‐service teachers in relation to the teacher–student relationship. Aims The purpose of this study was to identify the predictors of pre‐service secondary teachers' relationships with their students. It was hypothesized that friendliness and extraversion, self‐efficacy in classroom management and in student engagement, and various discipline strategies would contribute to the teacher–student relationship in terms of influence and affiliation. Sample A total of 120 pre‐service teachers in teacher education programmes participated. Method Data on pre‐service teachers' background (e.g., gender and age), personality traits, and self‐efficacy were gathered with teacher questionnaires; data on teachers' discipline strategies and the teacher–student relationship with student questionnaires. Results The two personality traits and self‐efficacy appeared not to be related to the teacher–student relationship in terms of affiliation or influence. However, significant relationships were found between the different discipline strategies and the teacher–student relationship in terms of influence and affiliation. There were differential effects for gender on the relationship between discipline strategies on the one hand and influence and affiliation on the other. Conclusion This study provides relevant new insights into the research fields of classroom management and interpersonal relationships in education. It contributes to our understanding of discipline strategies by fine tuning an existing instrument and revealing interesting connections with the teacher–student relationship. Specific gender effects on this connection are discussed, as are implications for practice.